Determinant Factors of Supervisor Model 4S (Structure, Skill, Support, Sustainability) Against the Implementation of Islamic Spiritual Care - Inggriane Puspita Dewi; Dewi Mustikaningsih (University of Muhammadiyah Malang, 2021)
Introduction: The supervision model commonly applied in nursing is the 4S model, namely the Structure, Skill, Support and Sustainability (4S) stages. This supervision model can be applied by the head of the room and the head of the shift as a supervisor in overseeing the implementation of Islamic spiritual nursing care in adult inpatient rooms. Purpose: to analyze the relationship between the role of the 4S supervisor model and the implementation of Islamic spiritual nursing care in adult inpatient rooms. Methods: the study used a cross sectional method. The sampling technique with a proportionate stratified random sampling was 62 nurses. Data analysis used univariate, bivariate analysis with Spearman test, and multivariate with logistic regression. Results: showed the role of the 4S supervisor model was good (88.7%), the implementation of Islamic nursing care was good category (52%), there was a relationship between the role of model supervision 4S with the implementation of Islamic spiritual care, with a significance value of <0.0001 and the strongest relationship between the 4S model and the implementation of Islamic spiritual care is the variable skill and sustainability, seen from the significance value for skills of 0.05 (Pvalue ≤0.05), and sustainability of 0.01 (Pvalue ≤0.05). The strength of the relationship is seen based on the OR [EXP B] value, respectively, skill (0.194) and sustainability (0.109). Discussion: The probability of nurses implementing Islamic nursing care well is 90% if they provide Islamic spiritual nursing care skills and continuous supervision by the hospital supervisor.